2021
DOI: 10.32859/era.21.45.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of veterinary practices from Gujjar and Bakarwal tribes of District Poonch, Jammu & Kashmir: A boon for animals from our ancestors

Abstract: Background: Gujjar and Bakarwal tribal communities are a treasure trove of traditional veterinary knowledge as they have been using plants to keep their livestock healthy and free from diseases for centuries. However, this knowledge is declining day by day due to several factors. The present study was aimed at surveying and documenting the medicinal plants used traditionally by the tribal communities of Gujjar and Bakarwal in the Poonch district of Jammu and Kashmir (J&K), India to treat livestock ailments.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Local people in the three bio-geographical regions employed a total of 148 plant species from 53 families that locals used for various purposes: medicine, fodder, tonic, antidote, and magic, as well as using them to protect not just themselves against ectoparasites but also animals (Supplementary Table 1). The current study's species numbers are higher than earlier fragmented ethno-veterinary studies from the same region, which focused mainly on one or a few districts in Jammu and Kashmir [e.g., (25)(26)(27)(28)(29)(30)]. By comparing the presently documented species with the allied areas (31-35), it became evident that J & K, in the Western Himalayan region, are more adept at utilizing plant resources for ethno-veterinary purposes than these parts of the Himalayas.…”
Section: General Plant Compositions and Distribution Patternsmentioning
confidence: 64%
“…Local people in the three bio-geographical regions employed a total of 148 plant species from 53 families that locals used for various purposes: medicine, fodder, tonic, antidote, and magic, as well as using them to protect not just themselves against ectoparasites but also animals (Supplementary Table 1). The current study's species numbers are higher than earlier fragmented ethno-veterinary studies from the same region, which focused mainly on one or a few districts in Jammu and Kashmir [e.g., (25)(26)(27)(28)(29)(30)]. By comparing the presently documented species with the allied areas (31-35), it became evident that J & K, in the Western Himalayan region, are more adept at utilizing plant resources for ethno-veterinary purposes than these parts of the Himalayas.…”
Section: General Plant Compositions and Distribution Patternsmentioning
confidence: 64%
“…In terms of districts, Poonch district represented the best-studied area as it contributes 27.7% of the total published articles. The high representation of district Poonch may be a fact of the particularly high biodiversity in the region (Dutta et al 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…Veterinary medicine is the science that deals with the prevention, treatment, or mitigation of disease and injury in animals, especially the domestic animals. Ethnoveterinary medicine is an offshoot of ethnobotany associated with the usage of traditional methods of medication of animals (Dutta et al 2021a. Due to insufficient or limited accessibility of allopathic medicine in several parts of the country, most livestock holders and farmers are still using the ancient plant-based traditional knowledge for the treatment of livestock ailments (Bhat et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, traditional herbal remedies provide effective and affordable therapies and widespread accessibility compared to western allopathic medicines (Ganesan et al 2008). Several previous studies have revealed pastoralists and farmers in India use plant species to safeguard livestock health (Ganesan et al 2008;Veena et al 2009;Phondani et al 2010;Maiti et al 2013;Pushpangadan et al 2016;Ahmad et al 2017;Radha et al 2020;Dutta et al 2021;Hassan et al 2022).…”
Section: Introductionmentioning
confidence: 99%